Directly grafting graphene oxide onto carbon fiber and the effect on the mechanical properties of carbon fiber composites. (5th March 2016) - Zhang, R.L.; Gao, B.; Ma, Q.H.; Zhang, J.; Cui, H.Z.; Liu, L.
Abstract: Amino-functionalized graphene oxide (GO-NH2 ) was directly grafted onto carbon fiber surface by covalent bonding in an attempt to improve the mechanical properties of carbon fiber composites. The effect of surface modification on the properties of carbon fiber and the resulting carbon fiber composites was investigated by X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and interfacial shear strength (IFSS). As revealed by Fourier transform infrared spectroscopy (FT-IR), GO-NH2 was successfully grafted on the carbon fiber surface. From dynamic contact angle analysis (DCAT) and XPS values, such GO-NH2 grafted carbon fiber exhibited significant improvements in surface energy and functional groups of the carbon fiber surface, which lead to an increase of 36.4% in the IFSS of its composites. Such hierarchical reinforcement shows great potential for enhancing interfacial properties in carbon fiber-reinforced composites. Graphical abstract: Highlights: Amino-functionalized graphene oxide was grafted onto carbon fibers by covalent bonding. The functionalized carbon fiber exhibited enhanced mechanical properties and interfacial adhesion. The functional groups on the hierarchical reinforcement are tunable to meet different demands.